2009
DOI: 10.1007/s12206-009-1001-4
|View full text |Cite
|
Sign up to set email alerts
|

Parallel implementation of finite volume based method for isoelectric focusing

Abstract: A message passing interface (MPI) based parallel simulation algorithm is developed to simulate protein behavior in non-linear isoelectric focusing (IEF). The mathematical model of IEF is formulated based on mass conservation, charge conservation, ionic dissociation-association relations of amphoteric molecules and the electroneutrality condition. First, the concept of parallelism is described for isoelectric focusing, and the isoelectric focusing model is implemented for 96 components: 94 ampholytes and 2 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Simulation work on IEF was performed with GENTRANS [21–30,37,49–55], other one‐dimensional simulators [59–64], and several multi‐dimensional simulators [31,65–73]. Most data dealing with pH gradient drifts were generated with GENTRANS.…”
Section: Computer Modeling Of Isoelectric Focusing On Ampholyte‐basedmentioning
confidence: 99%
“…Simulation work on IEF was performed with GENTRANS [21–30,37,49–55], other one‐dimensional simulators [59–64], and several multi‐dimensional simulators [31,65–73]. Most data dealing with pH gradient drifts were generated with GENTRANS.…”
Section: Computer Modeling Of Isoelectric Focusing On Ampholyte‐basedmentioning
confidence: 99%
“…Recently, due to the availability of high performance computers and the development of efficient parallel algorithms, it is possible to simulate several hundred ampholytes in order to form smooth profiles for both narrow-and broad-range IEF. 6,7 Although the aforementioned IEF simulations have been used to explain experimental behavior in 1-D 8,9 and twodimensional (2-D) [10][11][12] problems qualitatively, none of these models have accounted for the effect of temperature. All previous IEF models were based on the same reference temperature, with no consideration of Joule heating in the capillary tube or microchannels.…”
Section: Introductionmentioning
confidence: 99%
“…This is why efforts of researchers have been devoted to increasing the speed of simulation of electromigration by the parallelization of computation. Two papers of the Dutta group by Shim et al [19] and Yoo et al [20] have shown how the partial differential equations for isoelectric focusing can be efficiently discretized to allow for open multi-processing (OpenMP) or message passing interface (MPI) parallelization, both of which have brought about an increase of the speed of computation. The group of Kler is also active in the simulation of electromigration techniques by using modern software means.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers of the Dutta group by Shim et al. [19] and Yoo et al. [20] have shown how the partial differential equations for isoelectric focusing can be efficiently discretized to allow for open multi‐processing (OpenMP) or message passing interface (MPI) parallelization, both of which have brought about an increase of the speed of computation.…”
Section: Introductionmentioning
confidence: 99%